A study on barriers of innovation in warehouses and distribution centers - Xia, Xuerong (2013)
Innovation is a revolutionary path for all companies under present global competition and it will remain as a power source to ensure companies survival. The purpose of this study is to investigate current situation of innovation, future innovation trends and barriers of innovation that are present in warehouse and distribution centers in the Singapore context. The research project was conducted through a questionnaire survey, which examines the current situation and barriers of innovation in warehousing and distribution centers, and through in-depth interviews with selected organizations, which allows a more extensive and more thorough study on barriers of innovation in those organizations. The analysis was carried out by quantitative and qualitative methods. Barriers found in this study could be valuable for warehouses and distribution centers, and even for policy makers to better promote innovative activities in this industry. Recommendations were provided from perspectives of the industry and Singapore government.